„C Z Ł O W I E K A (TERAZ), O MUZO, WYPOWIEDZ”1 . PRÓBA ROZPOZNANIA ARTYSTYCZNEGO KSZTAŁTU DRAMATU NORWIDA KLEOPATRA I CEZAR - Trzcionka, Joanna (Colloquia Litteraria, 2012)
An Attempt to identify the artistic form of Norwid’s drama ‘Cleopatra and Ceasar’ The article concentrates on the analysis of lyrical excerpts form Norwid’s Cleopatra and Caesar while taking into account the title hero’s utterance and the form of the world created in the drama. The author creates a research methodology which allows her to define precisely the lyrical structure of Norwid’s historical drama